Development and operation of an indoor mass COVID-19 vaccination clinic - Gowe, Ivan W.; Crist, David; Kiteley, Brittany; Owens, Caitlin; Giddens, Adrienne (International Journal of Infection Control, 2021)
During the coronavirus disease 2019 (COVID-19) pandemic, many public response activities were conducted outdoors to reduce the risk of transmission. This was in adherence to existing infection prevention recommendations. We report the development and safe, efficient operation of a mass COVID-19 vaccination clinic during a time when guidelines for indoor clinics were limited.